2017
DOI: 10.1111/bph.13854
|View full text |Cite
|
Sign up to set email alerts
|

Selective κ receptor partial agonist HS666 produces potent antinociception without inducing aversion after i.c.v. administration in mice

Abstract: Background and purposeThe κ receptor has a central role in modulating neurotransmission in central and peripheral neuronal circuits that subserve pain and other behavioural responses. Although κ receptor agonists do not produce euphoria or lead to respiratory suppression, they induce dysphoria and sedation. We hypothesized that brain‐penetrant κ receptor ligands possessing biased agonism towards G protein signalling over β‐arrestin2 recruitment would produce robust antinociception with fewer associated liabili… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
80
0

Year Published

2017
2017
2023
2023

Publication Types

Select...
5
4

Relationship

1
8

Authors

Journals

citations
Cited by 64 publications
(81 citation statements)
references
References 51 publications
(82 reference statements)
1
80
0
Order By: Relevance
“…The same study investigated the behavioral effects of HS665 and HS666 in vivo. Interestingly, neither of these agents significantly impacted motor performance at any time point and HS666 did not induce CPP/CPA (Conditioned Place Preference/Conditioned Place Aversion) while HS665 produced significant place aversion when administered 5 times their analgesic ED 90 [ 62 ]. It is not clear if HS666 did not show CPA because it was a partial agonist or if this was because of its G-protein bias.…”
Section: Kor Biased Agonismmentioning
confidence: 99%
“…The same study investigated the behavioral effects of HS665 and HS666 in vivo. Interestingly, neither of these agents significantly impacted motor performance at any time point and HS666 did not induce CPP/CPA (Conditioned Place Preference/Conditioned Place Aversion) while HS665 produced significant place aversion when administered 5 times their analgesic ED 90 [ 62 ]. It is not clear if HS666 did not show CPA because it was a partial agonist or if this was because of its G-protein bias.…”
Section: Kor Biased Agonismmentioning
confidence: 99%
“…More recently, triazole 1.1 was shown to induce dose-dependent, KOPr-mediated antinociception and to suppresses chloroquine phosphate-induced scratching responses in C57BL/6 mice without affecting ambulatory behaviors in mice (Brust et al, 2016). Furthermore, antinociception devoid of dysphoria promoted by a KOPr-selective, G-protein-biased agonist, was demonstrated also by other authors (Spetea et al, 2017). On the other hand, White and co-workers have reported that the G protein-biased KOPr agonist RB-64 induces antinociceptive effects in the hot-plate test without impairing rotarod performance or novelty-induced locomotion.…”
Section: Discussionmentioning
confidence: 65%
“…b-arrestin 2 recruitment at KOPr was investigated by using the DiscoveRxPathHunter ® eXpressb-arrestin2 assay (Eurofins-DiscoveRx, CA, USA) according to manufacturer's recommendations and previously published procedures (Zhou et al, 2013;Spetea et al, 2017). Briefly, U2OS cells provided with the kit and stably co-expressing the kappa receptor and the enzyme acceptor-tagged b-arrestin2 fusion protein were seeded in cell plating medium into 96-well plates (10,000 cells per well) and maintained for 48 h at 37°C.…”
Section: B-arrestin 2 Recruitmentmentioning
confidence: 99%
“…Drug candidates targeting this G protein-coupled receptor (GPCR) have been developed for neuropsychiatric disorders [ 2 ] and pain [ 3 , 4 ]. The concept of biased agonism [ 5 ] that distinguishes between GPCR activation and β-arrestin mediated signaling pathways has shown promise in the development of KOR-based analgesics with fewer side effects [ 6 , 7 ]. This is important for the development of new treatments for neuropathic pain (NP), which occurs in about 7% of the US population [ 8 ].…”
Section: Introductionmentioning
confidence: 99%